KEPUTUSAN MEMILIH TABUNGAN SYARIAH: PERAN PENGETAHUAN DAN MEDIASI SIKAP - Azizati, Shili; Aang Gunaepi, Aang Gunaepi; Finantyo Eddy Wibowo, Finantyo Eddy Wibowo (JSE: Jurnal Sharia Economica, 2026)
Indonesia has great potential to become a global center for the Islamic economy through regulatory support and a strong Muslim population base. However, low Islamic financial literacy in Indonesia poses a fundamental challenge in optimizing the potential of the national Islamic banking sector. This study aims to analyze the influence of knowledge on people's decisions in choosing Islamic savings products, with attitude as an intervening variable. Using quantitative methods, data were collected through a survey of 384 respondents in Tasikmalaya City, who were determined using purposive sampling techniques. Data analysis was performed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with the help of SmartPLS. The results show that knowledge has a positive and significant effect on attitude (0,726) and decision (0,288). In addition, attitude has a positive effect on decision (0,570) and is proven to significantly mediate the effect of knowledge on decision (0,414). These findings confirm that attitude is a crucial factor that strengthens the relationship between knowledge and decision. The implication is that strategies to improve Islamic financial literacy should focus on forming positive attitudes in order to increase public participation in the Islamic financial sector.